Do real interest rates converge across Latin american countries? - Wen Long, Zhang (2018)
In this study, we apply the Sequential Panel Selection Method (SPSM), pro- posed by Chortareas and Kapetanios (Journal of Banking and Finance 33:390–404, 2009), to investigate and assess the non-stationary properties of the real interest rate parity (RIRP) for fourteen Latin American countries. Utilizing the SPSM, we can classify the entire panel into a group of stationary series and a group of non-stationary series. We clearly identify how many and which series in the panel are stationary processes and provide robust evidence that clearly indicate RIRP holds true for ten countries. Our findings note that these countries’ real interest rate convergence is a mean reversion toward RIRP equilib- rium values in a non-linear way. Our results have important policy implications for these Latin American countries under study.